Diurnal and semidiurnal tide-induced lateral movement of Ronne Ice Shelf, Antarctica - Makinson, K; Matt King; Nicholls, KW; Gudmundsson, GH (2012)
Recent GPS observations from a spatially extensive network across Ronne Ice Shelf show significant daily ice flow variations. At all sites, the almost-synchronous horizontal displacements occur at diurnal and semidiurnal tidal periods. During spring tides, displacements, velocities and strains near the ice front have superimposed oscillations that are +-300% of their mean values and occur over a six-hour period, resulting in regular ice shelf flow reversals. Close to ice stream grounding lines, however, the horizontal diurnal and semidiurnal signals decay and almost vanish. From our analysis, we conclude that ice shelves respond primarily elastically to tidal tilting, thus accounting for the observed diurnal and semidiurnal flow variations, and their amplification toward the ice shelf front. Our findings suggest that detailed modeling of these data could provide improved ice shelf and ice stream models for correctly simulating ice shelf flow and predicting future ice sheet evolution.